2018
DOI: 10.3390/ijerph15071395
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Disorder and Obesity-Related Outcomes among Women in Chicago

Abstract: Neighborhood psychosocial stressors like crime and physical disorder may influence obesity-related outcomes through chronic stress or through adverse effects on health behaviors. Google Street View imagery provides a low-cost, reliable method for auditing neighborhood physical disorder, but few studies have examined associations of Street View-derived physical disorder scores with health outcomes. We used Google Street View to audit measures of physical disorder for residential census blocks from 225 women age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 53 publications
0
38
0
2
Order By: Relevance
“…remain understudied with respect to their relationship with CVD risk. However, both have been demonstrated to associate with PA [59•-61] and weight status [62, 63, 52•].…”
Section: The Role Of Neighborhood Social Environment Factors In Pa Anmentioning
confidence: 99%
See 4 more Smart Citations
“…remain understudied with respect to their relationship with CVD risk. However, both have been demonstrated to associate with PA [59•-61] and weight status [62, 63, 52•].…”
Section: The Role Of Neighborhood Social Environment Factors In Pa Anmentioning
confidence: 99%
“…For example, a recent longitudinal study found a negative relationship between neighborhood disorder and scores on the Physical Activity Scale for the Elderly (PASE, mean difference=−2.0 units in PASE score [95% C.I.=−3.6, −0.3]) at baseline, but no association between disorder and PASE score after 2 years of follow up [60]. In contrast, a cross-sectional study examining the association between physical disorder (based on 311 complaint reports) and BMI indicated no association between them [62].…”
Section: The Role Of Neighborhood Social Environment Factors In Pa Anmentioning
confidence: 99%
See 3 more Smart Citations